Gandhi and his Jewish Friends - Chatterjee, Margaret. author. aut Link
XIV, 182 p.
Keywords: Most of Gandhi's associates in South Africa were Jewish. They were brought together through a common interest in theosophy and became deeply involved in Gandhi's campaigns, looking after his affairs when he was away in London or India. This book looks at the association between the two groups.